Formulasi Dan Uji Mutu Fisik Sediaan Sirup Pereda Nyeri Dari Ekstrak Kayu Manis (Cinnamomum burmanii) Dengan Variasi Konsentrasi Sukrosa - Meisya Salsabila; Nur Ermawati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Cinnamon (Cinnamomum burmanii) is a plant that is used as a medicinal raw material among the community, which contains eugenol with analgesic activity. The purpose of this study was to determine the effect of variations in the concentration of sucrose as a sweetener on the physical quality test of cinnamon extract syrup preparations and find out the best formulations with taste components preferred by the public. The research method uses an experimental method, cinnamon is extracted by maceration using a 70% ethanol solvent. This study was made with 3 formulations, with sucrose variations, namely F1 (62%), F2 (64%) and F3 (66%). Physical quality tests include organoleptic, homogeneity, viscosity, pH, clarity, displaced volume and hedonity. The results showed that variations in sucrose concentrations of 62%, 64%, and 66% had a significant effect on the viscosity value, where the higher the sucrose concentration, the viscosity would increase. The conclusion of this study, the best formula of cinnamon syrup preparations, namely formulation 3 (66%) has the best physical quality test and produces the most popular taste component for respondents.